Program Aplikasi Pengeluaran Dan Penerimaan Kas Berbasis Web Menggunakan Php Pada PT. Gunung Samarinda - Efry Ependi Saputra; Heldalina; Muhammad Syahid Pebriadi (Indonesian Journal of Applied Accounting and Finance, 2022)
The purpose of this study was to determine the information system of cash receipts and disbursements and to produce a web-based application program for cash receipts and cash disbursements using PHP at PT. Gunung Samarinda.This research method is using case studies with interviews, documentation and direct observation. The types of data used are qualitative and quantitative data types. In this study it was found that all records of cash receipts and disbursements were still using Microsoft Excel. Therefore, the authors suggest using a web-based cash receipt and disbursement application program design in order to help PT. Gunung Samarinda so that the current system is more effective and efficient.